1927 Mich. Pub. Acts 891,An Act to Regulate and License the Selling, Purchasing, Possessing and Carrying of Certain Firearms, § 9. - (:unkn) unknown (General Publisher, 1927)
Required registration for the owners of pistols
--
Keywords: REGISTRATION